2018
DOI: 10.3390/ma11050820
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Babassu Natural Filler on PBAT/PHB Biodegradable Blends: An Investigation of Thermal, Mechanical, and Morphological Behavior

Abstract: Blending of biodegradable polymers in combination with low-price organic fillers has proven to be a suitable approach to produce cost-effective composites in order to address pollution issues and develop products with superior mechanical properties. In the present research work PBAT/PHB/Babassu composites with 25, 50, and 75% of each polymer and 20% of Babassu were produced by melting extrusion. Their thermal, mechanical, and morphological behavior was investigated by differential scanning calorimetry (DSC), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Reduction in tensile strength due to fiber addition was also described in PHB composites with jute and hemp fibers (Gunning et al 2013); crude lignin-rich residues (Angelini et al 2014); PBAT/babassu fibers (Beber et al 2018); and almond shell, rice husk, and seagrass (Sánchez-Safont et al 2018). As reported by Beber et al (2018) and Sánchez-Safont et al (2018) elongation at break dropped when incorporating fibers in all composites analyzed.…”
Section: Mechanical Propertiessupporting
confidence: 54%
See 2 more Smart Citations
“…Reduction in tensile strength due to fiber addition was also described in PHB composites with jute and hemp fibers (Gunning et al 2013); crude lignin-rich residues (Angelini et al 2014); PBAT/babassu fibers (Beber et al 2018); and almond shell, rice husk, and seagrass (Sánchez-Safont et al 2018). As reported by Beber et al (2018) and Sánchez-Safont et al (2018) elongation at break dropped when incorporating fibers in all composites analyzed.…”
Section: Mechanical Propertiessupporting
confidence: 54%
“…Reduction in tensile strength due to fiber addition was also described in PHB composites with jute and hemp fibers (Gunning et al 2013); crude lignin-rich residues (Angelini et al 2014); PBAT/babassu fibers (Beber et al 2018); and almond shell, rice husk, and seagrass (Sánchez-Safont et al 2018). As reported by Beber et al (2018) and Sánchez-Safont et al (2018) elongation at break dropped when incorporating fibers in all composites analyzed. Furthermore, Sánchez-Safont et al (2018) found a more severe decrease in tensile strength and elongation at break with increasing fiber content, while Young's modulus presented a slight increase also dependent on fiber content.…”
Section: Mechanical Propertiessupporting
confidence: 54%
See 1 more Smart Citation
“…Polyhydroxybutyrate (PHB) and poly(butyleneadipate-co-terephatalate) (PBAT) were melted extruded with 20% of Babassu, an indigenous tree of some regions of Brazil. By using DSC technique, they observed the crystallization inhibition, whilst the use of Babassu, which did not affect the melting behaviour, allowed the tuning of crystallization and the plasticization [ 13 ]. They demonstrated the key role of DSC measurements in keeping the solid state at higher temperatures for designing products able to work at high temperatures.…”
Section: Thermal Techniques In Biopolymers’ Designmentioning
confidence: 99%
“…To improve the properties of PHB, many attempts have been studied by copolymerization [2,8,9,10,11,12] and blending [13,14,15] with the other polymers. The PHB-based copolymers have been extensively studied using infrared (IR) [16,17,18,19] and Raman [8,10,20] spectroscopies, wide-angle X-ray scattering (WAXS) [11,20,21], X-ray diffraction (XRD) [22,23], differential scanning calorimetry (DSC) [24,25], and so on.…”
Section: Introductionmentioning
confidence: 99%